(untitled) (Revista NUPEART, 2023)
This article discusses reflections on transmission processes that seek to encompass the multiplicity of bodies based on some principles that pay attention to the particularities of each person. Based on the author’s experience in dancing with groups of minoritized and stigmatized people, the issue of ableism, inclusion and the importance of welcoming and learning from the experience of otherness is discussed.